Organisation culture, IT infrastructure and KM process influencing KM effectiveness in a Malaysian manufacturing company / Nur Sakinah Ramli ... [et al.] - Ramli, Nur Sakinah; Kamal Ariffin, Nuriza; Che Muhammad, Siti Asiah; Sharkawi, Sharizan (Faculty of Business and Management, 2022)
This study aims to examine the relationship between Organisation culture, IT infrastructure and Knowledge Management Process, towards Knowledge Management implementation effectiveness in a Malaysian manufacturing company. This study was conducted among the permanent employees across all departments in the GLC Manufacturing Plant in Malaysia. Quantitative data were collected using self-administered questionnaires to a sample of 108 permanent employees. Based on the findings from multiple regression analysis, Organisation Culture had the most significant impact towards KM implementation effectiveness; whilst IT Infrastructure had a significant relationship but KM Process had no significant relationship with KM implementation effectiveness. The study had made significant contribution where it extended the literature on KM enablers influencing KM implementation effectiveness and contribute towards strategizing better policies on organizational culture and IT Infrastructure to improve overall KM effectiveness in manufacturing organization.